The Shortened Dental Arch Concept: Awareness and Opinion of Dentists in Lahore, Pakistan - Dr. Hafiz Muhammad Aamir Riaz; Sara Qureshi; Dr. Qudsia Iqbal; Dr. Insha Ajmal Malik; Dr. Muhammad Waseem Ullah Khan; Dr. Momina Akram (ziauddin University, 2024)
Abstract: Background: This study aims to assess the awareness and application of the shortened dental arch concept by the dentists of Lahore, Pakistan; and evaluate dentists' appraisal regarding the patients' responses on SDA application in terms of chewing function, oral comfort and dental appearance. Method: A self-administered questionnaire was voluntarily filled by 250 anonymous dentists of Lahore, Pakistan. Data was statistically analyzed using SPSS software version 25. This descriptive cross-sectional study was conducted in Lahore, Pakistan from 1-12-2021 to 1-06-2022 for a period of seven months. Results: More than half of the respondents (51.6%) were unaware of the SDA concept. A positive correlation was found between the awareness of the SDA concept and clinical experience of dentists. Only 32.6% of the 'aware' dentists had clinically implemented the SDA concept in the past one year. Chewing function and oral comfort of patients with SDA was presumed to be fairly acceptable by 40.8% (102) and 46.4%(116) of the dentists respectively. Conclusion: Majority of the responding dentists had paucity of knowledge regarding the SDA concept. A significant proportion of dentists perceived the chewing function, oral comfort and dental appearance to be fairly satisfying in individuals with shortened dental arches.